Weld pool surface temperature measurement from polarization state of thermal emission. Issue 1 (2nd January 2016) - Coniglio, Nicolas; Mathieu, Alexandre; Aubreton, Olivier; Stolz, Christophe
Abstract : This paper presents a passive polarimetry method using a division of aperture optical device in order to measure the temperature distribution at the weld pool surface. Thermal emission from a hot liquid metal was investigated at a near-infrared wavelength corresponding to a blind spectral window of a helium plasma generated during gas tungsten arc welding process. The refractive index of liquid metal and the surface radiance are deduced from the polarisation state of thermal emissions. Based upon the knowledge of both characteristics, the temperature distribution can be calculated.